204k views
2 votes
Factor 15x³-5x+6x-2 by grouping. What is the resulting expression?

O (5x²+2)(3x-1)
O (5x²-2)(3x+1)
O (15x+2)(x-1)
O (15x²-2)(x+1)

User Rashan
by
5.0k points

1 Answer

6 votes

Answer: Choice A.
(5\text{x}^2+2)(3\text{x}-1)

==================================================

Work Shown:


15\text{x}^3-5\text{x}^2+6\text{x}-2\\\\(15\text{x}^3-5\text{x}^2)+(6\text{x}-2)\\\\5\text{x}^2(3\text{x}-1)+2(3\text{x}-1)\\\\(5\text{x}^2+2)(3\text{x}-1)\\\\

Step-by-step explanation:

The idea is to pair up the terms into two groups. Factor each group separately. Then we pull out the overall GCF (3x-1) to finish up the factorization. You can use the FOIL rule to expand out the answer to get the original expression again, which helps confirm the answer.

User Khawar Islam
by
6.2k points